The SAGE encyclopedia of criminal psychology, 4 - Morgan, Robert D. (SAGE Publications, Inc., 2019)
The SAGE Encyclopedia of Criminal Psychology will be a modern, interdisciplinary resource aimed at students and professionals interested in the intersection of psychology (e.g., social, forensic, clinical), criminal justice, sociology, and criminology. The interdisciplinary study of human behavior in legal contexts includes numerous topics on criminal behavior, criminal justice policies and legal process, crime detection and prevention, eyewitness identification, prison life, offender assessment and rehabilitation, risk assessment and management, offender mental health, community reintegration, and juvenile offending. The study of these topics has been increasing continually since the late 1800s, with people trained in many legal professions such as policing, social work, law, academia, mental health, and corrections. This will be a comprehensive work that will provide the most current empirical information on those topics of greatest concern to students who desire to work in these fields. This encyclopedia is a unique reference work that looks at criminal behavior primarily through a scientific lens. With over 500 entries the book brings together top empirically driven researchers and clinicians across multiple fields - psychology, criminology, social work, and sociology - to explore the field
Keywords: Criminal psychology -- Encyclopedias; Kriminalpsychologie; Enzyklopädie